Effect of Incorporation of Tribulusterrestris (Gokshura) on pH of Cooked Chevon Sausages - Noor, Subha; Bhat, Fyaz (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A Study was undertaken to explore the possibility of utilization of Tribulusterrestris(Gokshura)as an alternative to synthetic preservatives in meat products. Chevon sausages were used as a model meat product and incorporated with different concentrations of Tribulusterrestris (0.25%, 0.50%, 0.75%) and were vacuum packed and assessed for pH under refrigerated (4±1oC) conditions at regular intervals of 0, 14, 28, 42 and 56 days. Incorporation of Tribulusterrestris significantly (P<0.05) lowered pH as compared to control.